2021
DOI: 10.1097/mcp.0000000000000833
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease risk assessment tools: is one better than the others?

Abstract: Purpose of reviewRisk assessment tools are essential in COPD care to help clinicians identify patients at higher risk of accelerated lung function decline, respiratory exacerbations, hospitalizations, and death. Recent findingsConventional methods of assessing risk have focused on spirometry, patient-reported symptoms, functional status, and a combination of these tools in composite indices. More recently, qualitatively and quantitatively assessed chest imaging findings, such as emphysema, large and small airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…This study also sought to determine the markers of clinically significant exacerbation and hospitalization [ 34 , 35 , 36 ]. We found that most of the clinical, physiological, and PRO measurements taken at the start were significant predictors of the first exacerbation and the first hospitalization caused by it, apart from BMI and the D-12 Affective score.…”
Section: Discussionmentioning
confidence: 99%
“…This study also sought to determine the markers of clinically significant exacerbation and hospitalization [ 34 , 35 , 36 ]. We found that most of the clinical, physiological, and PRO measurements taken at the start were significant predictors of the first exacerbation and the first hospitalization caused by it, apart from BMI and the D-12 Affective score.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we collected medical information of patients and focused on the cases with around 2-year follow-up records of HRCT and respiratory function tests. We combined HRCT data with indices of lung function for evaluating progress of the disease ( 14 ). This is the first report to compare the cumulative progression rate between patients with artificial stone-associated silicosis and non-artificial stone-associated silicosis.…”
Section: Introductionmentioning
confidence: 99%
“… 15 However, solely relying on peripheral blood eosinophils to guide personalized corticosteroid treatment may be inadequate, and all available clinical data should be taken into consideration. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%